Choosing Ethics Over Morals: A Possible Determinant to Embracing Artificial Intelligence in Future Urban Mobility - Kassens-Noor, E.; Siegel, Josh; Decaminada, Travis (Frontiers in Sustainable Cities, 2021)
Artificial Intelligence (AI) is becoming integral to human life, and the successful wide-scale uptake of autonomous and automated vehicles (AVs) will depend upon people's willingness to adopt and accept AI-based technology and its choices. A person's state of mind, a fundamental belief evolving out of an individual's character, personal choices, intrinsic motivation, and general way of life forming perceptions about how society should be governed, influences AVs perception. The state of mind includes perceptions about governance of autonomous vehicles' artificial intelligence (AVAI) and thus has an impact on a person's willingness to adopt and use AVs. However, one determinant of whether AVAI should be driven by society's ethics or the driver's morals, a “state of mind” variable, has not been studied. We asked 1,473 student, staff, and employee respondents at a university campus whether they prefer an AVAI learn their owners own personal morals (one's own principles) or adopt societal ethics (codes of conduct provided by an external source). Respondents were almost evenly split between whether AVAI should rely on ethics (45.6%) or morals (54.4%). Personal morals and societal ethics are not necessarily distinct and different. Sometimes both overlap and discrepancies are settled in court. However, with an AVAI these decision algorithms must be preprogrammed and the fundamental difference thus is whether an AI should learn from the individual driver (this is the status quo on how we drive today) or from society incorporating millions of drivers' choices. Both are bounded by law. Regardless, to successfully govern artificial intelligence in cities, policy-makers must thus bridge the deep divide between individuals who choose morals over ethics and vice versa.